Soil water dynamics under cereal and forage legume mixtures on drained Vertisols in the Ethiopian highlands - Abiye Astatke; Mohamed-Saleem, M.A.; El Wakeel, A. (Elsevier, 1995)
At the Debre Zeit Station Cereals (wheat and maize) and forage legumes (lablab, cowpea, vetch and clover) were grown as sole crops and as cereal/forage combinations on the broadbeds separated by drainage furrows (BBF). This is an improved land management system, developed by ILCA in collaboration with other national and international partners, to raise productivity of Vertisols. Soil water content monitored at soil depths of 0-50 cm and 50-100 cm indicated that lablab and cowpea deplete significantly greater amounts of available soil water during the growing season than vetch and clover. Deep rooted forage legumes lablab, cowpea and vetch are more suitable for combination with cereals such as maize than with wheat due to the phenological differences between the two crop types. Grain yields of wheat and maize were higher when intercropped with legumes than as sole crops in the absence of external N input. Moisture use by the various crop-forage land use types are discussed.